Determinación de procesos de programas de posgrado que integran el sistema de gestión de la organización educativa de la ESPAM MFL - Daza Estrella, Denisses Carolina (2024)
The objective of this work was to establish the processes of graduate programs that integrate the management system of the educational organization, as a contribution to the fourth-level academic management at ESPAM MFL. For its development, field, documentary and descriptive research were applied to obtain, detail and analyze the information. For the diagnosis of the current context of the processes, two interviews were conducted, one with the director of quality management and the other with the director of postgraduate and continuing education at ESPAM MFL, confirming that despite being described and documented, the processes and sub-processes have not yet reached their full maturity, so they must be updated. Then, the AVA methodology was applied to the student admission processes; allocation of scholarships; academic planning; modular portfolio and postgraduate degree, determined through the Value Added Index, inefficiency due to the existence of failures, such as: delay in the start of the program, non-delivery of documents by students and involuntary failures of the General Secretariat. Therefore, a proposal was prepared to update the manual of processes and procedures in force, through a restructuring of the processes of the graduate programs analyzed, with improvement actions that will serve as a guide for each person in charge, contributing to a general and specific planning of the processes studied, mitigating failures.